Effectiveness of Grading on Population Growth Performance for Giant Gourami (Osphronemus gourami) in Selection Program - Sularto (EDP Sciences, 2021)
Selection programs applied to fish commodities can be done through some structured stages. The grading process is one of the critical stages of the selection program. Grading can be done by selecting a group of fish in a population that has the best growth performance. Fish groups that selection criteria for the next are maintained populations. The purpose of the study was to determine the effectiveness of grading on the growth of the gourami. This research conducted strains of giant 1gourami Jambi, Kalimantan, Majalengka, and Tasikmalaya strains.The first grading with fish body weight criteria was carried out by the time the gourami population was 11 months old, so it was obtained sub population in three sizes. Each strain is then nurtured separately. After each population months-old gourami, each individual was tagged, then maintained communally until 25 months old. Results of the experiment suggest that grading is apparently effective in affecting giant gourami growth significantly differences (P< 0.05). The implications of this research can be applied in the huge gourami selection program to produce superior strain.